Blogging Agricultural News: A New Technology to Distribute News Real-Time - Blair L. Fannin; Edith A. Chenault (Journal of Applied Communications, 2005)
Web logging–or blogging–is gaining popularity on the Internet. Much like online diaries, blogs are short-text entries posted to a Web site in reverse chronological order. Writers can also include digital photos, audio, and video on their blogs. That popularity has not gone unnoticed. Several national publications including the New York Times and the Wall Street Journal have adopted blogs on their news Web sites. The main attraction of blogs is their immediacy–readers do not have to wait for the morning newspaper or the news on the hour. As soon as news breaks, the information can be posted to the blog. Having studied this technology’s growing popularity, communications specialists at Texas A&M University Agricultural Communications decided to experiment with blogging. The 2004 Beef Cattle Short Course at Texas A&M in August 2004 presented the perfect opportunity to try Web logging and to gauge interest from journalists and nonmedia consumers. The three-day short course annually draws more than 1,000 ranchers to Texas A&M to hear presentations about developments in cattle research, technology and equipment. In the past, the volume of presentations and information at the short course limited the number of timely news stories generated and distributed from the event. The blog was used to gauge the amount of news generated by the two communications specialists assigned to cover the event and to see if it would attract journalists and nonmedia consumers. The experiment included laptop computers and wireless Internet access. Select journalists were asked to participate in the experiment. They were asked to view the blog and offer feedback. A site meter also kept statistics on the number of visits to the blog.